3=5y

Simple and best practice solution for 3=5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=5y equation:


Simplifying
3 = 5y

Solving
3 = 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
3 + -5y = 5y + -5y

Combine like terms: 5y + -5y = 0
3 + -5y = 0

Add '-3' to each side of the equation.
3 + -3 + -5y = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -5y = 0 + -3
-5y = 0 + -3

Combine like terms: 0 + -3 = -3
-5y = -3

Divide each side by '-5'.
y = 0.6

Simplifying
y = 0.6

See similar equations:

| 3d+6d=9square | | -6v=-8v-10 | | 3x-7=x+2+2x | | 2w-8w=42 | | 3(x+2)+6=3x-12 | | -3(x-1)+1=1 | | 24k+11-5k-4= | | 8b^2-65b+8=0 | | -5+4f=3+6f | | 2(10h-10)-9= | | 35=x*2.5 | | 12e=100+8 | | 5(m+3)+2(m+8)= | | -5s=5-10s | | -3c+10c+2+-5= | | 0=x*2.5 | | 4x^2-14+2=0 | | 40+55h=190 | | 2k^4+12k^2+9=0 | | 0.3+y=2 | | 4x^2+44x-122=0 | | 6j+6=9j | | -5a+28a= | | 0=x/2.5 | | 9p-13p+12p+19q= | | 2(4.5+m)+3=4(m-3)+5.5 | | 2(4.5+m)+3=4(m-3)5.5 | | 2x+-1-6=10+-10x+6 | | 12d+5e-7d= | | 1=4.5-2p+2.333333p | | 5k(k-2)-8k=-34 | | 1+x-6x=11 |

Equations solver categories